The Impact of Trade Volume and Port Capacity in Southeast Asia Post-US-China Trade War: A Case Study of the Port of Singapore - Tita Syafira.S; Fazle Mawla.P; Maritza Firdhie Kayla; Abdel Aulia. A; Marcel Khairan (Sean Institute, 2025)
This study examines the impact of the US–China trade war on trade volume shifts and port capacity dynamics at Singapore Port, the leading transshipment hub in Southeast Asia. Escalating tariffs between the two major economies triggered supply chain restructuring, rerouting of shipping lines, and increased reliance on alternative logistics pathways within ASEAN. Using a descriptive qualitative method and secondary data from MPA, PSA International, UNCTAD, WTO, and related academic sources, the findings reveal that despite global uncertainty leading to overall trade slowdowns, Singapore maintained its operational resilience through digitalization, efficiency improvements, and the expansion of the Tuas Mega Port. Strong network connectivity and an integrated maritime ecosystem underpin Singapore’s competitiveness amid global trade disruptions, even as high dependency on transshipment remains a long-term strategic vulnerability.